Recombinant tumor necrosis factor alpha does not inhibit the growth of African trypanosomes in Axenic cultures - Kitani, H.; Black, Samuel J.; Nakamura, Y.; Naessens, Jan; Murphy, N.; Yokomizo, Y.; Gibson, John P.; Iraqi, F.A. (American Society for Microbiology, 2002)
Mice whose tumor necrosis factor alpha (TNF-) genes were disrupted developed higher levels of parasitemia than wild-type mice following infection with Trypanosoma congolense IL1180 or T. brucei brucei GUTat3.1, confirming the results of earlier studies. To determine whether TNF- directly affects the growth of these and other bloodstream forms of African trypanosomes, we studied the effects of recombinant mouse, human, and bovine TNF- on the growth of two isolates of T. congolense, IL1180 and IL3338, and two isolates of T. brucei brucei, GUTat3.1 and ILTat1.1, under axenic culture conditions. The preparations of recombinant TNF- used were biologically active as determined by their capacity to kill L929 cells. Of five recombinant TNF- lots tested, one lot of mouse TNF- inhibited the growth of both isolates of T. brucei brucei and one lot of bovine TNF- inhibited the growth of T. brucei brucei ILTat1.1 but only at very high concentrations and without causing detectable killing of the parasites. The other lots of mouse recombinant TNF-, as well as human TNF-, did not affect the growth of any of the test trypanosomes even at maximal concentrations that could be attained in the culture systems (3,000 to 15,000 U of TNF-/ml of medium). These results suggest that exogenously added recombinant TNF- generally does not inhibit the growth of African trypanosomes under the culture conditions we used. The impact of TNF- on trypanosome parasitemia may be indirect, at least with respect to the four strains of trypanosomes reported here.